Emotional intelligence and perceived negative emotions in intercultural service encounters: Building and utilizing knowledge in the banking sector - Thrassou, Alkis; Santoro, Gabriele; Leonidou, Erasmia; Vrontis, Demetris; Christofi, Michael (My University, 2020)
Purpose: This paper aims to explore the perceived negative emotions of both customers and frontline service employees (FSEs) during intercultural service encounters (ICSEs); and the building and utilization of corresponding knowledge in the banking sector. Design/methodology/approach: To reach the paper’s goal, a qualitative approach through semi-structured interviews conducted in the context of the banking industry is developed and presented. Findings: The findings presented and discussed the “perception of emotion” and the building of corresponding knowledge about ICSEs. Specifically, FSEs and foreign customers were found to be capable of perceiving negative emotions, both their own and of others. The authors further identified an array of emotions and feelings that facilitate the understanding of how ICSEs can be managed and improved. The findings finally highlight the degree and nature of the importance of building and storing knowledge on ICSEs soft processes, which are termed a key asset for service companies. Originality/value: An encounter between a service provider and a customer of different cultural backgrounds can become complex and critical. Despite this, there is not enough empirical evidence neither on the socio-psychological processes that take place during these encounters nor on how different ethnic groups develop interpersonal trust within the service sector. This research offers empirical insights regarding the means of detecting emotions and of improving the quality and management of knowledge on ICSE.
Keywords: Banking sector; Emotional intelligence; Intercultural service encounters; Knowledge management; Negative emotions